Budget Accountability in The Perspective of Habermas Communicative Action Theory - Mahdalena, M.; Haliah, H.; Syarifuddin, S.; Said, Darwis (Manunggal Halim Jaya, 2021)
Objectively, the purpose of this study is to produce a concept of accountability that is free from domination, which can synergize the accountability of the executive, legislative, and community and is oriented towards the liberation of communication. The expected result of this research is to be able to contribute, both theoretically and practically. The ideas from this research can be used as a reference for other researchers to test empirically with different approaches. Virtually, this research provides an idea for the opening of space for the public to be actively involved in all stages of the public accountability process to give input or criticism in the context of policy-making. To explore social reality as empirical material, the collaboration of several methods in this research was carried out as follows: Observation and interviews. Furthermore, based on the collected data, it will be netted and grouped based on specific categories and codes. Based on the previous description, this study produces a concept of accountability which the author calls triple accountability. Practically in the author's view, this concept is quite effectively implemented. This view adopts Habermas's communicative action theory that communication based rationality effectively overcomes social problems in human life, including government order.